A conceptual model for psychological empowerment of telecentre users - Mat Aji, Zahurin; Mohd Yusof, Shafiz Affendi; Sheik Osman, Wan Rozaini; Yusop, Nor Iadah (Canadian Center of Science and Education, 2010)
The Information and Communication Technologies usage among rural communities can be promoted through community telecentres. To date, there is a lack of adequate knowledge in terms of civic participation and empowerment that are related to ICT programs evaluations.This paper proposes a conceptual model for evaluating psychological empowerment of telecentres users based on review of literature.The Zimmerman’s constructs of empowerment theory that include intrapersonal, interactional and behavioural components form the basis of the model. Researchers in the area can used this model to examine the relationship among the components of psychological empowerment for different populations and settings, and create an avenue for understanding individual users of telecentre projects.